Teaching When the World Is on Fire - Friedman, Tanya (Radical Teacher, 2020)
This book review of Teaching When the World Is on Fire, a collection of essays edited by Lisa Delpit, discusses some of the strengths of the collection, highlights particularly useful chapters and reflects on ways the volume might have better achieved the explicit and implicit goals set forth by the editor.